Towards an Environment to Support Requirements Formalisation - Castro, Jaelson Freire Brelaz de; Gautreau, Christian Jean; Céspedes, Marco Antonio Toranzo (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 1996: Anais do X Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.1996.24444, 1996)
A major issue in requirements engineering is how to bridge the gap between ill-defined application situations and production of precise, formal specification of functional requirements. Although various formal languages have been proposed in the literature, practitioners still have great difficulties specifying requirements in their chosen formal language. One way of overcoming this barrier is to integrate formal techniques with existing methodologies (CORE, OMT, etc) and providing tool support for building formal specifications incrementally. In this paper we present The Multiview Tool, which addresses the problem of capturing requirements in the context of formal specification. Multiview enables multiple stakeholders to express their viewpoints based on a number of interrelated models, written in a variety of different notations. A detailed description of the project of the Multiview is provided. We start with the System Interface Context Diagram and a general overview of the tool Domain. A critical part of this domain is elaborated in terms of an Information Model. We also show one of the metamodels supported by the tool (Object Class representation schema). Several Interface Prototypes are also presented, together with an Object Message Model for a specific scenario. Statecharts are used to represent the behaviour of editors supported by the tool.